Plant Breeding Reviews. - Janick, Jules (Plant Breeding Reviews., 2011)
Plant Breeding Reviews presents state-of-the-art reviews on plant genetics and the breeding of all types of crops by both traditional means and molecular methods. Many of the crops widely grown today stem from a very narrow genetic base; understanding and preserving crop genetic resources is vital to the security of food systems worldwide. The emphasis of the series is on methodology, a fundamental understanding of crop genetics, and applications to major crops. The series is sponsored by the American Society for Horticultural Science and appears in the form of one or two volumes per ye.